MBRS-28. SINGLE-CELL TRANSCRIPTOME ANALYSIS OF MEDULLOBLASTOMA. Issue 2 (22nd June 2018) - Hovestadt, Volker; Filbin, Mariella G; Bihannic, Laure; Shaw, McKenzie L; DeWitt, John M; Groves, Andrew; Smith, Kyle S; Hadley, Jennifer; Gajjar, Amar; Robinson, Giles W; Mayr, Lisa; Slavc, Irene; et al.
Abstract: Human cancers are composed of cells with heterogeneous genetic and epigenetic states, resulting in substantial phenotypic diversity. Medulloblastoma (MB), a clinically challenging, malignant childhood brain tumor, is no exception. A better understanding of its cellular heterogeneity is urgently needed in order to develop more efficacious therapeutic strategies that eliminate all tumor subclones underlying MB initiation, maintenance, progression, and relapse. We used single-cell RNA sequencing to assess intratumoral heterogeneity in 20 MB samples representing all four molecular subgroups. Fresh surgical biopsies were dissociated and flow sorted into single cells prior to full-length transcriptome sequencing using the Smart-seq2 protocol. Computational analyses conducted on >6, 000 single cells identified cellular hierarchies ranging from proliferative, undifferentiated cell types to more differentiated neural- and astrocyte-like progeny. Transcriptional differences in undifferentiated cell populations between MB subgroups suggested distinct cellular origins, and informed oncogenic pathways believed to promote MB pathogenesis. Identification of transcriptional programs active in single cells aided the deconvolution of published bulk RNA-seq profiles, providing a deeper understanding of the heterogeneity characteristic of Group 3/4 subtypes. Lastly, inference of copy-number variations and probable driver-gene mutations from the single-cell data provided evidence for genetic subclones in a subset of patients. Overlaying transcriptional profiles on MB genetic subclones unveiled how oncogenic programs adapted during tumor evolution. These interim results provide unparalleled insights into the cellular heterogeneity of MB subgroups. Analyses aimed at further resolving molecular substructure in Group 3/4, verifying the developmental origins of MB subgroups, and implicating defined cell populations driving tumorigenesis are ongoing.